Dietary patterns and associated factors of schooling Ghanaian adolescents - Abdul-Razak Abizari; Zakari Ali (BMC, 2019)
Abstract Background Assessment of single nutrients or foods does not normally reflect the diet of population groups. Dietary pattern analyses are useful in understanding the overall diet and its relationship with disease conditions. The objective of the present study was to determine the dietary patterns and associated factors among schooling adolescents in Northern Ghana. Methods A cross-sectional study involving 366 pupils in 10 junior high schools in the Tamale metropolis was conducted. A Food Frequency Questionnaire (FFQ) which consisted of 60 commonly consumed foods was used to assess pupils' 7-day intake. Foods grouped (14) from FFQ data based on shared nutritional value were used to identify dietary patterns using principal component analysis (PCA). Bivariate and multivariate logistic regression analyses were used to determine the association between identified patterns and sociodemographic, anthropometric status, and household characteristics of pupils. Results Half of the pupils were female (50.3%) and average age was 15.6 ± 2.0 years. PCA identified two dietary patterns which in total explained 49.7% of the variability of the diet of pupils. The patterns were sweet tooth pattern (STP) with high factor loadings for sugar sweetened snacks, energy and soft drinks, sweets, tea and coffee, and milk and milk products, and a traditional pattern (TP) which showed high factor loadings for cereals and grains, local beverages, nuts, seeds and legumes, vegetables, and fish and seafood. Logistic regression showed that pupils who lived with their parents [AOR = 1.95; 95% CI (1.1-3.4); p = 0.019], those who went to school with pocket money [AOR = 4.73; 95% CI (1.5-15.0); p = 0.008], and those who lived in the wealthiest homes [AOR = 3.4; 95% CI (1.6-7.5); p = 0.002)] had higher odds of following the STP. The TP was associated with high dietary diversity (p = 0.035) and household wealth [AOR = 3.518; 95% CI (1.763-7.017); p < 0.001)]. None of the patterns was associated with anthropometric status of pupils. Conclusion Adolescents in the present study followed a sweet tooth or a traditional diet pattern which associated more with household- and individual-level factors but not anthropometric status.